Economic Growth and CO2 Emission in ASEAN: Panel-ARDL Approach - Feriansyah, Feriansyah; Nugroho, Hari; Larre, Aura Asyda; Septiavin, Qori’atul; Nisa, Cintya Khairun (Economics and Finance in Indonesia, 2022)
This paper investigates the relationship between economic growth and CO2 emissions from 1994 to 2018 using a panel approach from eight ASEAN countries. We found an established result using the Panel ARDL Pooled Mean Group method. First, the panel Cointegration analysis shows a significant long-term relationship between GDP and CO2 emissions. Second, the error correction mechanism shows a stable and consistent value. Third, we found that GDP has a significant long-term effect on CO2 emissions in ASEAN countries. Fourth, our results also show that GDP significantly impacts CO2 emissions in the short term for four countries: Indonesia, Malaysia, Thailand, and Cambodia. Based on these empirical results, implications and policy recommendations are presented. ASEAN countries should implement green growth policies by encouraging economic development which does not suppress the environment.